Singaporean youths and Daoist spirit mediums - Chan, Phyllis Ying Yi (Nanyang Technological University, 2023)
There has been a huge decline in Daoist Singaporean youths in the past few years. Organisational efforts have been in place to shift the focus away from folk Daoism, such as spirit mediums, to Daoist philosophical elements in attempts to attract and retain youths. However, a significant number of youths are still consulting Daoist spirit mediums. Hence, to understand why young Singaporeans consult spirit mediums, 36 respondents were recruited, in total, physically from five temples and virtually on social media platforms, and open-ended interviews were conducted. Results show that young Singaporeans consult spirit mediums regarding problems of various natures. Youths also visit spirit mediums to form personal connections with deities, receive emotional support and wisdom on moral values from deities. Effectiveness of previous consultations and the sense of family and community at temples also encouraged youths to revisit spirit mediums. Generally, findings indicate that Daoist spirit mediums play an important role in the secular, rational and modern lifestyles of Singaporean youths. Findings also indicate some of the struggles that young Singaporeans face when consulting spirit mediums. Based on the findings, interventions to better support these youths are suggested.